STUDI TINGKAT KEPUASAN PENGHUNI RUSUNAWA GAMALAMA TERNATE TERHADAP KUALITAS LINGKUNGAN DAN BANGUNAN - Ilyas, Isma; Ahadian, Edward Rizky; Yuda S, M. Taufik; Irnawaty, Irnawaty (Fakultas Teknik Universitas Khairun, 2024)
The limited service capability of rent-based flats in meeting the needs of residents will affect the living satisfaction conditions of the residents. Rusunawa Gamalama has several problems, such as garbage and poor ceiling conditions. The purpose of this study was to determine the level of resident satisfaction with the quality of the environment and buildings in Rusunawa Gamalama Ternate. Data collection was carried out by distributing questionnaires to residents of the Gamalama flat. Percentages are used to analyze environmental and building quality satisfaction. The results showed that the quality of the environment resulted in an average level of 67.32% which means satisfaction. The highest value was found in the sub-variable of regional location conditions, namely 90.10%, and the lowest value was found in the sub-variable of social environment, namely 52.12%. At the same time, the level of building quality produces an average of 75.47% which means satisfaction. The highest value was found in the floor sub-variable, namely, 91.81%, and the lowest was found in the roof covering sub-variable, 39.69%).